Recent studies of tort and civil liability - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Review of the collective monograph in three books: Responsibility in the right: philosophy, history, theory, Bezklubyy I., S. Bobrovnik, I. Gritsenko, etc .; Liability in Private Law: I. Bezklubyy, N. Kuznetsov, Maidanyk R. et and Responsibility in public law: P. Andrushko, VI Bezklubyy, A. Berlach etc.